High School Students' Online Learning Ineffectiveness in Experimental Courses During the COVID-19 Pandemic - Hong, Jon-Chao; Liu, Yue; Liu, Yinsheng; Zhao, Li (Frontiers in Psychology, 2021)
Due to the COVID-19 pandemic, online learning has been adopted in all stages of education. This sudden change from traditional learning to 100% online learning may affect students’ learning effectiveness, especially in experimental courses. However, there has been little discussion of experimental courses conducted entirely through online learning. To address this gap, the present study investigated factors affecting high school students’ online learning ineffectiveness (OLI) in online experimental courses, particularly online science experimental courses. The role of gender was also explored to understand whether it affects participants’ OLI. An ANOVA was conducted to analyze the data from a survey of 347 online learners in high schools. The results indicated that the number of online experimental courses and the duration of online hands-on learning were negatively related to the high school students’ OLI. Meanwhile, the study found that the high school participants’ OLI differed by gender, with female students more likely than males to have OLI in the context of online learning. The results of this study can provide a reference for teachers who conduct online experimental courses and wish to improve their online teaching, not only during the COVID-19 lockdown, but also in other pandemic periods.